Chemical control of branched broomrape in processing tomato using sulfonylureas in southern Italy - Conversa, Giulia; Bonasia, Anna; Elia, Antonio (Italian Journal of Agronomy, 2017)
The present research investigated the efficacy and the selectivity of three sulfonylureas (SUs) rimsulfuron (RS), chlorsulfuron (CS) and triasulfuron (TS) for Phelipanche ramosa control in processing tomato. In 2014 a single dose (D) (75, 15 and 22.5 g ha–1 active ingredient – a.i.– of RS, CS and TS, respectively), split into three applications at equal rate, was delivered into the soil layer interested by the roots using two herbigation methods i) through the drip irrigation system (DH) or ii) by foliar spray followed by overhead irrigation (FH). In 2015 SUs were applied in pre-transplant at one third of D, and in post-transplant at the dose D, at onehalf and at one-fourth of D, delivered in 3 rates by drip herbigation. In both experiments RS gave the best broomrape control and the highest yield increase compared with the untreated crop and CS improved crop yield similarly to RS despite being less effective in contrasting branched broomrape, In 2014, the foliar application of TS and CS resulted in plant injuries which, more significantly with TS, caused lower numbers and fresh weight of fruits as well as a lower crop productivity increase. In the same year the drip herbigation with TS resulted in the lowest broomrape control and tomato yield increase. In 2015, the best parasite control and tomato yield performances were obtained with RS and CS when applied in pre-transplant at 25.0 and 5.0 g ha–1 a.i., respectively, and in post-transplant at 75.0 and 15.0 g ha–1 a.i., respectively. With TS, the pre-transplant application a.i. was the most effective among the TS treatments resulting in a yield improvement similar to RS and CS, while it was confirmed the low broomrape control when applied through drip irrigation due to its low mobility in the soil. More research is needed in order to better exploit the combination of pre- and post-transplant applications in the chemical control of P. ramosa of tomato under the conditions in southern Italy.